Edukasi Minat Bakat dalam Bijak Bermedia Sosial di SDN Pakujaya 02 - Imelda Imelda (PT Hakhara Akademia Indonesia, 2025)
Many children are hesitant to speak in front of an audience. Children tend to follow what happens in their surroundings because they feel unable to recognize their interests and talents. This tendency causes children to give up easily and not fully maximize their self-exploration. In the digital era, social media can be a means to explore themselves. However, social media hurts children's cognitive, social, and emotional development without proper guidance and education. The purpose of this activity is to create a creative educational space by using social media to recognize the interests and talents of students at SDN Pakujaya 02 Banten. The technique used is to convey education on how to utilize social media wisely, incorporating persuasive and creative public speaking. The results of this activity can encourage learning motivation, recognize interests and talents, increase self-confidence in public appearances, and foster digital awareness from an early age. The high enthusiasm for this activity demonstrates that children are highly motivated to recognize their interests and talents and are increasingly confident in exploring them through social media.